On pharmacological neuroenhancement as part of the new neurorights' pioneering legislation in Chile: a perspective - Cornejo-Plaza, María Isabel; Saracini, Chiara (Frontiers in Psychology, 2023)
The so-called neurorights are emerging human rights, or rather reconfigurations of already existing human rights, seeking to address the impact of the possible misuse of neurotechnologies, which have the potential to become more invasive and harmful in the future if not regulated.The aim of specifying neurorights is to protect the dignity and autonomy of the individual in the face of neurotechnological advances. Recently, Chile proposed a Constitutional reform inspired by the neurorights, opening a debate. One of the proposed neurorights is fair and equitable access to cognitive enhancement, which will be the specific object of this perspective article. Starting from the legal proposal, we analyse and discuss some perspectives on cognitive enhancement, or "neuroenhancement", which could be considered as part of enhancement neurotechnologies, pointing out that pharmacological enhancers, or "smart drugs", might be considered as part of these enhancers. We present a classification of the different types of cognitive enhancements as it has been proposed in the literature, into which pharmacological cognitive enhancement can be included, concluding that there is currently no agreement amongst scholars and lawyers about the ethical consideration of pharmacological cognitive enhancement.We therefore argue that it is necessary for the legislator to explicitly address the issue in the proposed regulations, in order to take a clear position on the topic, as it has been done in the United Kingdom, where the pharmacological neuroenhancers have been explicitly excluded from the regulation. If pharmacological neuroenhancers are going to be considered neurotechnologies, then new law proposals should seek harmonization with the already existing legislation regulating pharmacological health and consumer rights (both globally, taking into account international drug laws, and locally, according to each country's internal regulations) and, of course, with the whole system of fundamental rights. Finally, we briefly discuss the ethical problem of equitable access to this new type of neurotechnologies (as part of the neurorights) and leave the debate open for new insights from the scientific community on the possible consequences of including (or not) pharmacological neuroenhancers as neurotechnologies for cognitive enhancement in the framework of the ethical and legal debate.